The Secret Garden - Seabag-montefiore, Mary; Burnett, Frances Hodgson Marks, Alan (Usborne Pub Ltd UK, 2008)
Presents an abridged version of the story of ten-year-old Mary who, after the death of her parents, comes to live in a lonely house on the Yorkshire moors where she discovers an invalid cousin and the mysteries of a locked garden.